STATUS IMUNITAS, ASI EKSKLUSIF, GIZI DAN LINGKUNGAN DENGAN KEJADIAN ISPA PADA BALITA DI PUSKESMAS REWARANGGA KECAMATAN ENDE TIMUR KABUPATEN ENDE PROPINSI NUSA TENGGARA TIMUR - Marieta K S Bai; Pius Kopong Tokan (Poltekkes Kemenkes Kupang, 2022)
Generally, ISPA usually attacked the children under five because of low of the body power and the immunity, wasn’t given exclusive Mother’s Milk, uncompleted immunization, the weather and the environment didn’t support too. The aim of research to analyze the relation of immunity, exclusive Mother’s Milk, nutrient and environment with the occurrence of ISPA to the children under five in Rewarangga Community Health Centre, East Ende Sub district, Ende Regency, East Nusa Tenggara Province. The sort of research was an analytical research by the Cross Sectional design. The populations for an examination 201, the number of the samples consisted of 60 people by the sampling purposive technic. The result of research showed that there was a meaningful relation among immunity, exclusive Mother’s Milk, nutrient and environment with the occurrence of ISPA to the children under five by the value of p < 0.005, namely immunity value p=0.013, exclussive mother’s milk p=0.011, nutrient p=0.008 and enviroment p=0.021. Based on the values above so could be concluded that the environmental factor which the biggest Influenced ISPA to the children under five and suggested in order that the children under five was able to examined in Rewarangga Community Health Centre accordance with the timetable that has been determined and tried to avoid the children under five from the pollution of the environment